Microplastics-based Water Pollution: A Review from Qur’anic Perspectives - Siti Aini Ameera Muhammad Amri; Robiatul Adawiyah Mohd @ Amat (USIM Press, 2024)
E-Proceeding Islamic Science Social Postgraduate Conference 2023 (ISSPeC 2023) “The Tradition of Knowledge as a Catalyst for the Sustainability of Civilization”/ editors : Anita Binti Ismail, Farah Laili Binti Muda @ Ismail, Kamal Azmi Bin Abd Rahman, Afi Roshezry Bin Abu Bakar, Ikmal Hafiz Bin Jamal Organized by: Institut Sains Islam (ISI) & Pusat Pengajian Teras (PPT) 30 November 2023